Environmental Security in South-Eastern Europe International Agreements and Their Implementation - Montini, Massimiliano; Bogdanovic, Slavko; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
Authored by international experts from academia, international organizations, governments and NGOs, this book highlights the main environmental security issues in the South-East European (SEE) countries, with a particular focus on climate change and water management. The common goal of the authors was to provide a reliable evaluation of whether existing legal regimes and correct implementation of applicable international treaties may contribute to reducing environmental security risks in the region. In-depth analyses and assessment of major challenges in compliance, serve as a firm ground which such evaluation is based on. This volume is recommended for public officials, legal practitioners and consultants. Its interest may also extend beyond the SEE countries, serving as a case-study of a broader and paradigmatic relevance of the analysis and management of environmental and security issues in a trans-boundary context.
The Role of International Organisations in Environmental Security Issues -- The Environment and Security Initiative in South Eastern Europe: Transforming Risk Into Cooperation -- The Role of UNESCO designated Sites in Fostering International Cooperation and Environmental Security in SEE -- Social and Environmental Issues related to Security in SEE Countries -- The Impact of International Treaties on Climate Change in SEE Countries -- The Impact of the International Treaties on Water Management in South-Eastern Europe -- Towards Environmental Security by Adapting the Energy Sector: Summary of Strategies and Opportunities for Technology Transfer and Cooperation in the SEE Region -- Challenges of Environmental Protection in Times of Armed Conflict -- Food Security and Eco-terrorism Impacts on Environmental Security through Vulnerabilities.-Emergency Situations and Risk Management in Multilateral Environmental Agreements: a Comparative Analysis in the SEE -- Large Scale Infrastructural Projects in South Eastern Europe and their Impact on Political Relations, Economic Development and Environmental Security -- Environmental Impact Assessment in a Trans-boundary Context in the SEE countries -- Promoting Environmental Protection within the Management of Shared Natural Resources between Albania and Montenegro: the Shkodra Lake Watershed -- Environmental Impact Assessment in a Trans-boundary Context in Montenegro -- The Framework Agreement of the Sava River Basin (FASRB).
Keywords: Law; Public law; Environmental law; Sustainable development; Law; European Law/Public International Law; Environmental Law/Policy/Ecojustice.; Sustainable Development